2018
DOI: 10.1111/1759-7714.12849
|View full text |Cite
|
Sign up to set email alerts
|

Chinese multidisciplinary expert consensus: Guidelines on percutaneous transthoracic needle biopsy

Abstract: Biopsy has been used to diagnose thoracic diseases for more than a century. Percutaneous needle biopsy plays a crucial role in the diagnosis, staging, and treatment planning for tumors in the lungs, thoracic wall, hilum, and mediastinum. With the continuous improvement in imaging techniques, the range of clinical applications for percutaneous needle biopsy is also expanding. It has become important to improve Chinese professionals’ and technicians’ understanding of percutaneous transthoracic needle biopsy (PTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 103 publications
(128 reference statements)
1
30
2
Order By: Relevance
“…Percutaneous needle biopsy is less invasive than surgical biopsy, and some of its complications, such as bleeding, infection, peritonitis, pleural injury, and pain, are more likely to be overlooked [ [6] , [7] , [8] ]. The most dangerous complication in liver biopsy is bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous needle biopsy is less invasive than surgical biopsy, and some of its complications, such as bleeding, infection, peritonitis, pleural injury, and pain, are more likely to be overlooked [ [6] , [7] , [8] ]. The most dangerous complication in liver biopsy is bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, common and serious complications of thoracic needle biopsy include not only bleeding but also pneumothorax. Pneumothorax was the most common complication according to two reports, occurring in 35% of patients who underwent thoracic needle biopsy [ 8 , 9 ]. The mortality rate was between 0.02% and 0.15% [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the operation's safety of metastasis along the needle tract has not yet been determined. Some studies have shown that this operation will have the risk of breast wall implant metastasis [1,2], pleural metastasis [3] [4]and so on, while other studies showed that this operation is safe in the diagnosis [5,6], and tumor metastasis along the needle track is relatively rare [7]. The purpose of this meta-analysis is to evaluate the risk of recurrence in patients with lung cancer caused by PTNB and to provide evidence-based medicine in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…But the operation's safety of metastasis along the needle tract has not yet been determined. Some studies have shown that this operation will have the risk of breast wall implant metastasis [1], pleural metastasis [2,3] and so on, while other studies showed that this operation is safe in the diagnosis [4,5], and tumor metastasis along the needle track is relatively rare [6]. The purpose of this metaanalysis is to evaluate the risk of recurrence in patients with lung cancer caused by PTNB and to provide evidence-based medicine in clinical diagnosis.…”
mentioning
confidence: 99%